The Role Of Competence As A Mediator In Employee Performance In Logistics Companies - Novia Clarissa; Yuddy Giovanna Priscilla (UNIVED Press, 2025)
This research aims to analyze the influence of Training, Work Motivation, Work Discipline, and Workload on Employee Performance Competence. The research sample includes 301 respondents who are employees in logistics companies in Batam City, using a quantitative research method. The measurement tool used in this study is Smart PLS. The results show that Training, Competence, Work Discipline, and Workload have a significant influence on employee performance. However, the influence of employee performance mediated by competence shows varied results. Training and Work Discipline mediated by competence have a significant relationship with employee performance, while Work Motivation is not significant. This provides important insights into the factors affecting the performance of logistics companies post-COVID-19 pandemic and provides a basis for the development of effective management strategies to address the challenges faced by this industry.